A complexidade do ser fictício: a construção da personagem Marcela no romance A ostra e o vento - Araújo, Lanaiza do Nascimento Silva (2012)
It is possible to notice that the modern narrative increasingly seeks to invest its characters with a broad and complex nature, away from the well-defined beings of the traditional narrative. Through this work, we aim to make a study of Marcela, a character of the novel A ostra e o vento, by Moacir Costa Lopes, taking into account the way the complexity of the fictitious being is constituted through an analysis of structural, semantic, and thematic elements. We first will bring up a brief theoretical discussion about the character in a novel, and we also will carefully analyze the diagetic universe, presenting the complex path of the character further. Subsequently, we will focus on the structure of the narrative which creates a complex picture of the character, using the technique of crossed points of view as well as the technique of temporal fragmentation. Finally, we will investigate conflicting social relations that portray Marcela s disturbed inner side, as well as the metaphoric symbolic language, which furnishes a number of different representation of this character, impeding the creation of a well-structured coherent character. Studies of scholars such as Antonio Candido, Anatol Rosenfeld, Vitor Manuel de Aguiar e Silva, Fernando Segolin, Gerard Genette, Michel Zéraffa, among others, will guide our analysis